Kaji Eksperimental Pengaruh Debit Udara dan Air terhadap Peningkatan Oksigen Terlarut pada Air Kolam Ikan Koi - Kahartoni, Kahartoni; Mawarni, Drajat Indah (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2023)
To optimize the koi fish farming business certainly faces a number of problems. Problems in koi ponds can certainly cause problems from slow growth to the death of all koi fish in the pond. Most of these problems stem from fish waste products that produce toxic ammonia. Based on the facts, we conducted an Experimental Study of the Effect of Air and Water Discharge on Dissolved Oxygen Increase in Koi Fish Pond Water in Kentong Village to obtain optimal parameters for Koi fish farming using a microbubble generator. The results of this study are in the form of graphs of increased oxygen levels and values for each variation of water discharge. The results of this study indicate that the longer the aeration process, the DO (dissolved oxygen) concentration in the water will increase. At a high water discharge it creates a high turbulence flow, so it can break the air into smaller pieces. Installing MBG can increase dissolved oxygen levels in water. Water discharge is more influential than gas discharge in increasing dissolved oxygen levels. The longer the aeration process, the DO concentration in the water will increase. The value of is strongly influenced by temperature, water characteristics and turbulence